Seasonal variation in semen quality and conception rate of Jaffarabadi buffalo bulls (Bubalus bubalis) in India - Hirabhai, Parmar Kirankumar; Hirjibhai, Tank Prafulchandra; Hirjibhai, Savsani Harishkumar; Bhagvanbhai, Vala Karsanbhai (Buffalo Bulletin, 2022)
The study was conducted on four Jaffarabadi breeding bulls, 5 to 6 years old, to know the neat characteristics based on total of 192 semen ejaculates evaluated and cryopreserved during winter (10 to 25°C mean temperature) of November to February (n=96 ejaculates) and summer (38 to 45°C temperature) March to June (n=96 ejaculates). The neat seminal characteristics of Jaffarabadi bulls, viz., ejaculate volume (ml), colour/density (score), sperm concentration (million/ml), mass activity (score), initial motility (%), live sperm (%), abnormal sperm (%), HOST reactive sperm (%) and acrosomal integrity (%), first AI conception rate observed during winter season were 5.19±0.18, 2.38±0.10, 1253.36±24.75, 3.73±0.05, 80.31±0.05, 86.20±0.64, 5.00±0.40, 85.75±0.43, 93.56±0.56, 45.75±0.21 respectively, whereas the respective values in summer were 5.07±0.13, 2.00±0.00, 1186.60±24.78, 3.72±0.11, 78.75±0.46, 82.31±0.74, 7.13±0.52, 84.93±0.45, 90.56±0.23, 43.50±0.11. The semen quality of fresh samples was observed better during winter compared to summer season for use in breeding program with satisfactory first AI conception rate.